Translation Procedures done by Visually Impaired Translator: An Annotated Study - Sunardi Sunardi; Raden Arief Nugroho; Budi Harjo; Muljono Muljono; Valentina Widya Suryaningtyas; Nina Setyaningsih; Anisa Larassati; Agus Sri Giyanti (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2022)
In understanding a language, people should consider the context usage such the cultural aspect and structure of the language itself. One of the study in translation is annotated translation. Jenny William and Andrew Chesterman reveal annotated translation is a translation with commentary. In this research, the researchers are challenged to know her ability in transferring Indonesian document, “Peraturan Gubernur Jawa Tengah No. 11 Tahun 2017”, a regulation of Central Java Governor to English by using annotated translation. This document contains an important information about fulfilling disabled people rights in Central Java. The researchers applied Larson’s theory in rendering the document. The translation process can be explored into 8 steps, those are preparation, analysis, transfer, initial draft, reworking initial draft, testing, polishing, and preparing the manuscript for the publisher. However, the researchers combined the processes by adding Agus Sri Giyanti’s own procedures as she is a visually impaired translator who was involved in this research. The procedures are converting the data and comprehending the text. This research also examines the classification of disability terminologies and their techniques used in translating the terms in order to establishing acceptable translation. In order to analyze the data, the researchers applied introspective and retrospective methodology. Introspective methodology is a method which is almost similar to the introspection of personal work. A retrospective study examines the factors of a causing problem by looking backward from the beginning of the study. This study firstly, aims at giving explanation for the disability terms on the Pergub Jawa Tengah No. 11 Tahun 2017. Secondly, to evaluate the ability of researcher in translating Indonesian regulation into English naturally. Last, since one of the researchers is a visually impaired translator, hopefully this study may provide some information on how the novice translator with visual impairment could translate Indonesian text into the English one independently.